2003
DOI: 10.1134/1.1601752
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the freeze-out temperature by the isospin thermometer

Abstract: The high-resolution spectrometer FRS at GSI, Darmstadt, provides the full isotopic and kinematical identification of fragmentation residues in relativistic heavy-ion collisions. Recent measurements of the isotopic distribution of heavy projectile fragments led to a very surprising new physical finding: the residue production does not lose the memory of the N/Z of the projectile ending up in a universal de-excitation corridor; an ordering of the residues in relation to the neutron excess of the projectile has b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…The fragments in the reactions analyzed above have neutron excesses of more than 20. In the 0.2A GeV 136 Xe +p [45], 0.5A GeV 136 Xe +p [46], 136 Xe + d [47], and 1A GeV 136 Xe +p [48] spallation reactions, fragments with I = 10 to 24 have been measured depicted in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…The fragments in the reactions analyzed above have neutron excesses of more than 20. In the 0.2A GeV 136 Xe +p [45], 0.5A GeV 136 Xe +p [46], 136 Xe + d [47], and 1A GeV 136 Xe +p [48] spallation reactions, fragments with I = 10 to 24 have been measured depicted in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…The simulation, relying on the BLOB model, 60 is compared to several experimental data measured at FRS (Darmstadt) for fragments produced in proton/deuteron-induced spallation and for fragments emitted by spectator sectors in relativistic peripheral ion-ion collisions. [61][62][63][64][65] clustering, counterbalanced by mean-field resilience effects, in hot (but not initially diluted) sources, such as the nuclear systems formed in spallation reactions. From these results it clearly emerges the important role of many-body correlations even in describing processes which are driven by mean-field instabilities.…”
Section: Discussionmentioning
confidence: 99%
“…10 for the isotopic component of the nuclide production in p+ 124 Xe, 136 Xe, 208 Pb at 1AGeV. [61][62][63][64][65] In particular, it is shown that the isotopic content of the lightest IMFs evolves in time from approximately the value of the target to a value which approaches but does not reach the residue corridor. 66 This effect 67 and the collapsing of all datasets on the same ridge for a given isotopic content is a well known signature of the presence of a limiting temperature in the disassembling of the system, in connection with the liquid-gas phase transition of nuclear matter.…”
Section: Spallation Reactions Induced By Relativistic Protons and Deu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, subsequent experimental [21] and theoretical [22,23] investigations were undertaken for these purposes. Furthermore, the emission of other products in spallation reactions, like pions [24], as well as complex heavy nuclei, were studied both experimentally [25][26][27] and theoretically [28][29][30][31]. In spite of these efforts, there remain problems which are not satisfactorily explained by existing models [32,33].…”
Section: Introductionmentioning
confidence: 99%